2021
DOI: 10.1177/21501327211024390
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Patients’ Connection to Referred Social Needs Resources at a Federally Qualified Health Center

Abstract: Introduction: In an effort to improve health outcomes and promote health equity, healthcare systems have increasingly begun to screen patients for unmet social needs and refer them to relevant social services and community-based organizations. This study aimed to identify factors associated with the successful connection (ie, services started) to social needs resources, as well as factors associated with an attempt to connect as a secondary, intermediate outcome. Methods: This retrospective cohort study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(61 reference statements)
2
8
0
Order By: Relevance
“…Our work has resulted in four student-led, peer-reviewed publications and eight presentations at state, national, international conferences focused on the development and implementation of the Help Desk model, adaptations of the program during the pandemic, evaluating factors associated with a successful patient referral, and patient-reported barriers to accessing referred resources ( 15 17 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work has resulted in four student-led, peer-reviewed publications and eight presentations at state, national, international conferences focused on the development and implementation of the Help Desk model, adaptations of the program during the pandemic, evaluating factors associated with a successful patient referral, and patient-reported barriers to accessing referred resources ( 15 17 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Between March 2019 and December 2020, student volunteers called 791 patients and successfully reached 501 (78%) of patients referred to follow-up by their case manager ( 17 ). Within 4 weeks of the initial referral, 63.3% of patients had at attempted to contact at least referred resource and 32.7% had started services with 1 or more of their referred resources ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 This is consistent with the implications found in a recent retrospective cohort study conducted at the same FQHC that found that a simplified, 'direct-access', and less complicated process for applying and receiving services was associated with a statistically significant increase in the odds of successfully connecting with a referred resource. 22 Additional qualitative research conducted with patients participating in the same social needs intervention at our FQHC also revealed that policy and societal level determinants related to resource availability and application processes were major barriers to referral success. 29 This study has several limitations.…”
Section: Discussionmentioning
confidence: 96%
“…18 Program details, including the screening instrument, workflows, and navigator training, are described in detail elsewhere. [19][20][21][22] On March 10, 2020, North Carolina declared a state of emergency for the COVID-19 pandemic. Due to pandemic safety precautions, between March 2020 and December 2020, case managers shifted from screening patients for social needs inperson to conducting proactive telephonic screening for the lowest income patients, identified through reports from the clinic's finance department.…”
Section: Program Description and Data Collectionmentioning
confidence: 99%